HUBUNGAN ANTARA EMOTIONAL ATTACHMENT DENGAN PERILAKU DIGITAL HOARDING SETELAH MENGALAMI PUTUS CINTA PADA INDIVIDU DI FASE DEWASA AWAL - Jocelyn Vania Ariadi; Ratriana Yuliastuti Endang Kusumiati (Journal of Innovation Research and Knowledge, 2026)
This study aims to examine the relationship between emotional attachment and digital hoarding among young adults following a romantic breakup. The research involved 231 participants and employed a correlational design. Data were collected using Likert-type instruments, namely the Emotional Attachment Scale (EAS) and the Digital Hoarding Questionnaire. Descriptive analysis showed that the mean level of emotional attachment among participants was in the moderate category, as was the level of digital hoarding. Statistical analysis using the Pearson Product-Moment correlation yielded a correlation coefficient of 0.374 with a significance level of (p<0,05) indicating a significant positive relationship between emotional attachment and digital hoarding. These findings suggest that individuals with stronger emotional attachment to digital memories tend to exhibit higher levels of digital hoarding behavior.